A new MgB2 bulk ring fabrication technique for use in magnetic shielding or bench-top NMR systems. (1st August 2022) - Moseley, D A; Wilkinson, D P; Mousavi, T; Dennis, A R; Speller, S; Durrell, J H
Abstract: We report a new methodology in bulk MgB2 ring production for use in small-scale magnetic shielding or bench-top nuclear magnetic resonance systems. This process is a modified field-assisted sintering technique (mFAST) which enables direct formation of the rings without the need for machining or additives into the precursor powder. The shielding and trapped field capabilities of three mFAST MgB2 rings were determined using zero-field- and field-cooled magnetic experiments. Individual bulks trap magnetic fields up to 1.24 T at 20 K comparable to the highest published data for a ring sample. It is anticipated that for many applications, multiple rings will be stacked to form the required experimental structure. We find, for the three ring stack, a trapped field of 2.04 T and a maximum shielded field of 1.74 T at 20 K. The major factor limiting performance at low temperatures are flux jumps which cause rapid loss of the trapped field or shielding capability. Preliminary studies of magnetic field ramp rate dependence on flux jumps were conducted illustrating that even at very slow ramp rates (0.007 T min −1 ) they remain a significant issue. Despite this concern, we conclude that mFAST represents an exciting new fabrication methodology for bulk MgB2 rings.